TRAPPED IN THE HYPOGLYCEMIA LOOP: A RARE CASE OF RAPIDLY PROGRESSIVE METASTATIC INSULINOMA - Lian, Zi Yang; Tong, Chin Voon; Hussein, Zanariah (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Malignant insulinomas are rare and account for approximately 10–15% of all insulinomas. Most metastatic insulinomas are not curable with surgery alone and necessitate a multimodal approach encompassing medical, locoregional, targeted, systemic, and supportive therapies. The optimal treatment sequence should be individualized to each patient. CASE A 21-year-old male presented with a one-month history of recurrent hypoglycemic episodes characterized by neuroglycopenic symptoms. Subsequent evaluation confirmed endogenous hyperinsulinemic hypoglycemia. Computed tomography (CT) imaging revealed a 2.1 x 2.0 x 1.8 cm lesion in the pancreatic tail, multiple liver lesions in both lobes (largest measuring 3.8 x 4.1 x 4.1 cm), and intra-abdominal lymphadenopathy (largest measuring 1.1 x 1.8 cm). Gallium-68 (Ga-68) DOTATATE PET/CT and fluorine-18 fluorodeoxyglucose (18F-FDG) PET/CT demonstrated predominantly somatostatin receptor-avid disease. Following multidisciplinary team discussion, the tumor was deemed inoperable. Medical management was rapidly escalated, involving diazoxide, hydrochlorothiazide, corticosteroids, octreotide followed by pasireotide, and dextrose infusion, guided by continuous glucose monitoring. Endoscopic ultrasound-guided fine needle biopsy (EUS-FNB) of the pancreatic tail lesion revealed a high-grade, well-differentiated neuroendocrine tumor (Ki67 50%, G3). While awaiting access to systemic therapies, including everolimus, peptide receptor radionuclide therapy (PRRT), and chemotherapy, the patient underwent radiofrequency ablation (RFA) of the pancreatic tail lesion and transarterial embolization (TAE) of the hepatic lesions. However, repeat imaging two months later demonstrated rapid progression, with diffusely scattered and enlarging liver metastases throughout both lobes (largest measuring 7.9 x 16.8 x 15.2 cm). The patient experienced frequent, severe hypoglycemic episodes requiring prolonged hospitalization, high-concentration dextrose administration via multiple central venous catheters, high-dose corticosteroids, and further escalation of medical therapy. Over the course of his hospitalization, he developed recurrent sepsis and multi-organ dysfunction, ultimately leading to his death. CONCLUSION This case illustrates the aggressive nature, management complexities and therapeutic challenges of metastatic insulinomas. Several studies demonstrated that early administration of systemic chemotherapy in high-grade insulinomas has been associated with improved survival. Early consideration of advanced therapies like everolimus, PRRT and chemotherapy may be crucial in managing malignant insulinomas.